Problemy estymacji parametrów w modelach dekompozycyjnych z dyskretną zmienną objaśnianą - Bąk, Andrzej (Problems of Parameters Estimation in Decompositional Models with Discrete Dependent Variables, 2005)
The paper presents some problems linked with nonmetric decompositional models. There are presented:- four types of measurement scales (especially discrete scales),- sources and consequences of consumer preferences heterogeneity,- nonmetric decompositional models included heterogeneity of preferences.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 180-189